Sodium selenate as a disease-modifying treatment for progressive supranuclear palsy: protocol for a phase 2, randomised, double-blind, placebo-controlled trial - Kelly L Bertram; Lucy Vivash; Dennis Velakoulis; Leonid Churilov; Thomas Kimber; David Darby; Terence J O’Brien; Charles B Malpas; Christopher M Hovens; Simon J G Lewis; Joanne Fielding; Andrew H Evans; et al. (BMJ Open)
Introduction Progressive supranuclear palsy (PSP) is a neurodegenerative disorder for which there are currently no disease-modifying therapies. The neuropathology of PSP is associated with the accumulation of hyperphosphorylated tau in the brain. We have previously shown that protein phosphatase 2 activity in the brain is upregulated by sodium selenate, which enhances dephosphorylation. Therefore, the objective of this study is to evaluate the efficacy and safety of sodium selenate as a disease-modifying therapy for PSP.Methods and analysis This will be a multi-site, phase 2b, double-blind, placebo-controlled trial of sodium selenate. 70 patients will be recruited at six Australian academic hospitals and research institutes. Following the confirmation of eligibility at screening, participants will be randomised (1:1) to receive 52 weeks of active treatment (sodium selenate; 15 mg three times a day) or matching placebo. Regular safety and efficacy visits will be completed throughout the study period. The primary study outcome is change in an MRI volume composite (frontal lobe+midbrain–3rd ventricle) over the treatment period. Analysis will be with a general linear model (GLM) with the MRI composite at 52 weeks as the dependent variable, treatment group as an independent variable and baseline MRI composite as a covariate. Secondary outcomes are change in PSP rating scale, clinical global impression of change (clinician) and change in midbrain mean diffusivity. These outcomes will also be analysed with a GLM as above, with the corresponding baseline measure entered as a covariate. Secondary safety and tolerability outcomes are frequency of serious adverse events, frequency of down-titration occurrences and frequency of study discontinuation. Additional, as yet unplanned, exploratory outcomes will include analyses of other imaging, cognitive and biospecimen measures.Ethics and dissemination The study was approved by the Alfred Health Ethics Committee (594/20). Each participant or their legally authorised representative and their study partner will provide written informed consent at trial commencement. The results of the study will be presented at national and international conferences and published in peer-reviewed journals.Trial registration number Australian New Zealand Clinical Trials Registry (ACTRN12620001254987).